Synthesis and Characterization of a Gel-Type Electrolyte with Ionic Liquid Added for Dye-Sensitized Solar Cells - Le-Yan Shi; Tien-Li Chen; Chih-Hao Chen; Kun-Ching Cho (International Journal of Photoenergy)
This study intends to develop the electrolyte needed in dye-sensitized solar cells (DSSCs). Moreover, three different ionic liquids in different molalities are added to the gel-type electrolyte. Experimental results show that the DSSC composed of the gel-type electrolyte with no ionic liquid added can acquire 4.13% photoelectric conversion efficiency. However, the DSSC composed of the gel-type electrolyte with 0.4 M of 1-butyl-3-methylimidazolium chloride added has an open-circuit voltage of 810 mV, a short-circuit current density of 9.56 mA/cm2, and photoelectric conversion efficiency reaching 4.89%. Comparing this DSSC with the DSSC with no ionic liquid added, the photoelectric conversion efficiency can be enhanced by 18.4%. As to durability, the DSSC composed of the gel-type electrolyte with ionic liquid added still has a photoelectric conversion efficiency of 3.28% on the 7th day after it is stored in an enclosed space and maintains 0.72% efficiency on the 14th day. When the proposed DSSC is compared with the DSSC prepared by using a liquid-type electrolyte, the durability of its photoelectric conversion efficiency can be increased by 7 times.